Dimensional Transitions in a Bose Gas - Sawitzki, Paul; Carmesin, Hans-Otto (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2021)
In the early universe, the density reached the order of the Planck density. As a result, there were gravitational instabilities in which dimensional transitions occurred. It should be taken into account that the early universe consists only of photons and black holes. Photons are bosons. The quantum physical model for many bosons, such as photons, is the Bose gas model. Here we can study the dynamics of the early universe more accurately (Hans-Otto Carmesin (2020): The Universe Developing from Zero-Point Energy Discovered by Making Photos, Experiments and Calculations. Berlin: Verlag Dr. Köster). This research aims to determine and apply the critical densities of dimensional phase transitions in Bose gases with the use of a computer simulation. This new type of phase transitions could be used in the future to apply them to the horizon problem. This might accordingly lead to the solution of the problem without including a hypothetical entity such as the so called *inflation field*. The project is presented as an example for teamwork in an ensemble of projects in the field of quantum gravity that are carried out in a research club at our school.